Recent advances in small RNA mediated plant-virus interactions. (19th May 2019) - Prasad, Ashish; Sharma, Namisha; Muthamilarasan, Mehanathan; Rana, Sumi; Prasad, Manoj
Abstract: Small RNAs (sRNA) are reported to play pivotal roles in the epigenetic and post-transcriptional regulation of gene expression during growth, development, and stress response in plants. Recently, the involvement of two different classes of sRNAs namely, miRNAs (microRNAs), and siRNAs (small interfering RNAs) in biotic stress response has been underlined. Notably, during virus infection, these sRNAs deploy antiviral defense by regulating the gene expression of the modulators of host defense pathways. As a counter defense, viruses have evolved strategic pathways involving the production of suppressors that interfere with the host silencing machinery. This molecular arms race between the sophisticated gene regulatory mechanism of host plants fine-tuned by sRNAs and the defense response exhibited by the virus has gained much attention among the researchers. So far, several reports have been published showing the mechanistic insights on sRNA-regulated defense mechanism in response to virus infection in several crop plants. In this context, our review enumerates the molecular mechanisms underlying host immunity against viruses mediated by sRNAs, the counter defense strategies employed by viruses to surpass this immunogenic response and the advances made in our understanding of plant-virus interactions. Altogether, the report would be insightful for the researchers working to decode the sRNA-mediated defense response in crop plants challenged with virus infection.